The First Report and Phylogenetic Analysis of Canine Distemper Virus in Cerdocyon thous from Colombia (2023)
Canine distemper virus (CDV) is the etiological agent of a highly prevalent viral infectious disease of domestic and wild carnivores. This virus poses a conservation threat to endangered species worldwide due to its ability to jump between multiple species and produce a disease, which is most often fatal. Although CDV infection has been regularly diagnosed in Colombian wildlife, to date the molecular identity of circulating CDV lineages is currently unknown. Our aim was to evaluate the presence and phylogenetic characterization of CDV detected in samples from naturally infected Cerdocyon thous from Colombia. We sequenced for the first time the CDV infecting wildlife in Colombia and demonstrated the presence of South America/North America-4 Lineage with a higher relationship to sequences previously reported from domestic and wild fauna belonging to the United States of America. Our results are crucial for the understanding of the interspecies transmission of CDV in the domestic/wild interface and for the prevention and control of such an important multi-host pathogen